Thermal ablation versus parathyroidectomy for secondary hyperparathyroidism: A meta-analysis. (October 2019) - Gong, Lifeng; Tang, Weigang; Lu, Jingkui; Xu, Wei
Abstract: Objective: Thermal ablation and parathyroidectomy (PTX) have been recommended for patients with secondary hyperparathyroidism (SHPT). However, it is uncertain which is the better method. The aim of the present meta-analysis was to evaluate the efficacy and surgical complications of the two treatment methods. Methods: The following databases were searched from inception to December 31, 2018: PubMed, EMBASE, the Cochrane Library, CNKI, and Wanfang. Eligible studies comparing thermal ablation and PTX for SHPT were included. Data were analysed using Review Manager Version 5.3. Results: Six studies were included in the meta-analysis. Four cohort studies and two randomized controlled trials involving 326 patients with SHPT were identified. There was no difference concerning parathyroid hormone (PTH) levels (MD 58.04, 95% CI -17.60–133.68, P = 0.13), calcium levels (MD -0.07, 95% CI -0.17–0.04, P = 0.21), phosphorus levels (MD 0.21, 95% CI -0.18–0.61, P = 0.29), or hoarseness (OR 0.53, 95% CI 0.24–1.16, P = 0.11) between the two surgical methods. Compared with PTX, thermal ablation reduced the risk of hypocalcaemia (OR 0.23, 95% CI 0.11–0.47, P < 0.01). However, thermal ablation increased the risk of SHPT persistence and/or recurrence compared with PTX (OR 4.24, 95% CI 1.44–15.76, P = 0.03). Conclusion: Thermal ablation and PTX were effective surgical approaches for SHTP. Thermal ablation reduced the risk of hypocalcaemia and increased the risk of SHPT persistence and recurrence. More large multicentre randomized controlled trials are necessary to confirm the conclusions. Highlights: Our meta-analysis revealed that thermal ablation and parathyroidectomy(PTX) were effective surgical approaches for secondary hyperparathyroidism (SHPT). After thermal ablation or parathyroidectomy(PTX), there was no difference in parathyroid hormone（ PTH）, levels, calcium levels, phosphorus levels, hoarseness. Thermal ablation reduced risk of hypocalcaemia compared with PTX. Thermal ablation increased risk of hyperparathyroidism persistence and/or recurrence compared with PTX.